Two Bariatric Surgical Procedures Differentially Alter the Intestinal Microbiota in Obesity Patients - Chen, Guolin; Zhuang, Jingshen; Cui, Qianwen; Jiang, Shuwen; Tao, Weihua; Chen, Wanqun; Yu, Shuqing; Wu, Lina; Yang, Wah; Liu, Fucheng; Yang, Jingge; Wang, Cunchuan; et al. (Obesity surgery, 2020)
Aims To explore the intestinal microbiota composition affected by the two most widely used procedures of bariatric surgery, laparoscopic sleeve gastrectomy (LSG) and laparoscopic roux-en-Y gastric bypass (LRYGB), in Chinese obesity patients. Methods Stool samples were collected from the obese patients before ( n = 87) and with follow-up after the surgery ( n = 53). After DNA extraction, 16S rDNA (V3 + V4 regions) sequencing was completed on Illumina HiSeq 2500 sequencing platform. The samples were analyzed base on four groups, pre-LSG ( n = 54), pre-LRYGB ( n = 33), post-LSG ( n = 33), and post-LRYGB ( n = 20). The linear mixed models were used to analyze the alteration of intestinal microbiota before and after the surgeries of LSG or LRYGB. Student’s t test and χ 2 test were used for analysis of independent groups; Metastats analysis was used to compare the relative abundance of bacteria, and Pearson correlation and Spearman correlation analysis were used to test the correlation between indicated groups. Results 87 patients were included and 53 (60.92%) of them completed the follow-up (9.60 ± 3.92 months). Body mass index (BMI) decreased from 37.84 ± 6.16 kg/m 2 to 26.22 ± 4.33 kg/m 2 after LSG and from 45.75 ± 14.26 kg/m 2 to 33.15 ± 10.99 kg/m 2 after LRYGB. The relative abundance of 5 phyla and 42 genera were altered after the surgery in the cohort. Although no alteration of Firmicutes was observed at phylum level, 54.76% of the altered genera belong to phylum Firmicutes . Both LSG and LRYGB procedures increased the richness and evenness of intestinal microbiota in obese patients after the surgery. Particularly, 33 genera altered after LSG and 19 genera altered after LRYGB, in which 11 genera were common alterations in both procedures. Conclusion Both LSG and LRYGB altered the composition of intestinal microbiota in Chinese obesity patients, and particularly increased the richness and evenness of microbiota. Genera belonging to phylum Firmicutes were the most altered bacteria by bariatric surgery. The procedure of LSG resulted in much more pronounced alteration of the intestinal microbiota abundance than that observed in LRYGB. While different genera were altered after LSG and LRYGB procedures, 10 genera were the common altered genera in both procedures. Bacteria altered after LSG and LRYGB were functionally associated with BMI, and with relieving of the metabolic syndromes.